FASHION TERM BORROWINGS FOUND IN ARTICLE TRANSLATION IN COLOURS MAGAZINE - I Gusti Agung Maitreya Adi Santa (Program Magister Linguistik Universitas Udayana, 2015)
This paper discusses the borrowing technique used to translate fashion terms.The theory of borrowing proposed by Molina and Albir (2002) and Pedoman Umum Ejaan Bahasa Indonesia Yang Disempurnakan (2009) were used to analyze the data. There are two types of borrowing which are found, namely: pure borrowing and naturalized borrowing. Pure borrowing is the process when a source language word or term is taken purely or without any changes to the receptor language. This is done by a translator to keep the textual meaning in the source language for the sake of the accuracy of meaning through the form. While naturalized borrowing takes words or terms in source language but they are then naturalized or adapted to the norm of the receptor language (mostly the spelling rule). This is done to increase the readability of receptor language text. The application of borrowing is mostly in the form of adjustments of the spelling based on Indonesian language norm. There are two reasons why the translator used the borrowing technique: a) The translator doesn’t find the equivalent of the word being translated in receptor language; b) The translator is eager to create the stylistic effect mostly in fashion or s/he considers the word in receptor language is less popular than source language word.